2019
DOI: 10.1109/access.2019.2911307
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Prognostic Approach for Newly Developed System With Three-Source Variability

Abstract: Remaining useful life (RUL) estimation is the key of prognostics and health management (PHM) technology and is an effective way to ensure the safe and reliable operation of equipment. Aiming at the lack of historical data and prior information for the newly developed small-sample systems, an adaptive RUL estimation method based on the expectation maximization (EM) algorithm is proposed with threesource variability. First, a degradation model based on a Wiener process is established to incorporate threesource v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Particularly, the PDF curves obtained by the proposed method are much sharper than those obtained by the method in [12], which further demonstrates that considering three-source variability can significantly improve the accuracy of the estimated RUL. Furthermore, the estimated RUL uncertainty of the proposed method decreases continuously as the sampling data are accumulated, which is particularly important in the field of the RUL prognostic and maintenance decision [31], [36]. To further quantify the comparison results, FIG.…”
Section: A Numerical Examplementioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, the PDF curves obtained by the proposed method are much sharper than those obtained by the method in [12], which further demonstrates that considering three-source variability can significantly improve the accuracy of the estimated RUL. Furthermore, the estimated RUL uncertainty of the proposed method decreases continuously as the sampling data are accumulated, which is particularly important in the field of the RUL prognostic and maintenance decision [31], [36]. To further quantify the comparison results, FIG.…”
Section: A Numerical Examplementioning
confidence: 99%
“…By comparing with the results obtained by focusing only on one or two sources variability, it was shown that considering threesource variability simultaneously can greatly improve the accuracy of the model fitting and the performance of the RUL estimation. In addition, the work in [36] developed a RUL prediction method with three-source variability to adaptively update the model parameters and the corresponding RUL distribution via the CM data up to date. However, the results of this work were based on a linear drift model.…”
Section: Introductionmentioning
confidence: 99%
“…The first way is combining the Bayesian updating and expectation maximization (EM) algorithm, which was first presented by Wang et al [34] for fitting an adapted Brownian motion-based model with a drifting parameter. Then, this updating mechanism has been generalized to the degradation model based on the basic Wiener process [31], [32], nonlinear process [35], [36], degradation process with three sources of variance [37], [38]. Based on the EM algorithm, the RUL estimation results could overcome the influences of imperfect prior information.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Si et al [6,28] applied this algorithm to the basic linear Wiener process. Subsequently, this mechanism was extended to the nonlinear Wiener process [46,47], the linear Wiener process with measurement error [48], the nonlinear Wiener process with measurement error [49,50] and other random effects models [51][52][53][54]. This joint parameter updating method can overcome the influence of imperfect prior information.…”
Section: Introductionmentioning
confidence: 99%